The Depictions of the Entire Lunar Cycle in Graeco-Roman Temples. Issue 1 (January 2016) - Priskin, Gyula
The scenes that have come down to us from Graeco-Roman temples depicting the entire lunar cycle can be classified into two major groups. The first comprises some unanimously interpreted cases which show a line of gods in procession towards the moon. The second group is made up of the more complex scenes found in the temples of Edfu, Dendera and Esna, for which either unsatisfactory or conflicting, sometimes even diametrically opposed interpretations have been put forward. All these problematic representations are reviewed here in order to present a unified analysis that, on the one hand, aims to unravel the subtleties of the iconographic details of the individual scenes and, on the other, to establish clear interconnections between them.